2010
DOI: 10.1002/mnfr.200900111
|View full text |Cite
|
Sign up to set email alerts
|

Oleuropein and hydroxytyrosol inhibit MCF‐7 breast cancer cell proliferation interfering with ERK1/2 activation

Abstract: The growth of many breast tumors is stimulated by estradiol (E2), which activates a classic mechanism of regulation of gene expression and signal transduction pathways inducing cell proliferation. Polyphenols of natural origin with chemical similarity to estrogen have been shown to interfere with tumor cell proliferation. The aim of this study was to investigate whether hydroxytyrosol (HT) and oleuropein (OL), two polyphenols contained in extra-virgin olive oil, can affect breast cancer cell proliferation inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
94
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(102 citation statements)
references
References 49 publications
(54 reference statements)
7
94
0
1
Order By: Relevance
“…2). These data are in agreement with those from other studies and confirm the involvement of oxidative stress in the oleuropein toxicity (44,45). In addition, our results suggest that DU145 cells show a different susceptibility to necrosis induced by oleuropein.…”
Section: Discussionsupporting
confidence: 93%
“…2). These data are in agreement with those from other studies and confirm the involvement of oxidative stress in the oleuropein toxicity (44,45). In addition, our results suggest that DU145 cells show a different susceptibility to necrosis induced by oleuropein.…”
Section: Discussionsupporting
confidence: 93%
“…6B), suggesting that oleuropein-induced HeLa cell death is dependent on the JNK signaling pathway that plays a critical role in inducing apoptosis. However, other reports suggest that oleuropein-induced apoptotic cell death is associated with NF-kB (58), HIF-1a (62), PI3K-Akt (17,63), ERK (64,65). Such differential effects observed from one study to another could reflect cell type or treatment specificity.…”
Section: Discussionmentioning
confidence: 97%
“…Some epidemiological studies showed correlation between olive products consumption and incidence of breast cancer. Due to its little mild side effects, oleuropein is required as one of the phenolic compounds in olive with a powerful effect on inhibiting the proliferation and migration of cancer cells (Sirianni et al, 2010;Santiago-Mora et al, 2011). Oleuropein can also target steps in cancer progression (Abe et al, 2011).…”
Section: Discussionmentioning
confidence: 99%